Removal of NO by Using Fe3+-H2O2 Mixed Reagent Solution in Lab-Scale Bubbling Reactor with Addition of EDTA - Guo, Rui-Tang; Yu, Yue-Liang; Pan, Wei-Guo; Jin, Qiang; Ding, Cheng-Gang; Guo, Shi-Yi (Asian Journal of Chemistry, 2013)
The removal of NO by using Fe3+-H2O2 mixed reagent solution with the addition of EDTA was investigated in a lab-scale bubbling reactor. The effects of pH value, H2O2 concentration, NO inlet concentration and reaction temperature were assessed. The experimental results indicated that addition of EDTA into Fe3+-H2O2 mixed reagent solution can improve NO removal efficiency under weakly acidic conditions. When NO concentration exceeded 600 ppm, the gas-liquid reaction between NO and absorption liquid was controlled by liquid-film. The removal efficiency of NO increased with increasing reaction temperature.